Benign tumors in gynecology and obstetrics. Fibroleiomioma management in the gravid state - puerperal. - Tejada Fernández, Víctor (2015)
11 clinics stories fibroleiomiomas were studied in the pregnant-puerperal state that occurred in 9552 births in the Department of Obstetrics Hospital Central North IPSS, between January 1971 and December 1980. It found that the frequency is relatively low 0.11%. The average patient age was 36 years. About 80% were primiparous and secundigestas. 54.4% were to term pregnancies and in the same proportion, the myomas were diagnosed preoperatively. The treatment is essentially surgical and according to the reproductive function. Myomectomy was performed in 72%; in 3 cases not made, laparotomy was subsequently performed in 2 patients, 1 uterine hypotonia and over by degeneration and tumor infection. 54% were unique fibroids: predominated of 2-10 cm. 72% were subserosal fibroids and 90.9% were found in the uterine body. Complications were by degeneration and puerperal infection and uterine hypotonia, so hysterectomy was performed in 2 cases. Nonoperative interventions for this cause was found during pregnancy. At 35.4%, the fibroids causing abnormal fetal presentations.